تحليل انتقادي للسياسات الضريبية السورية - القاضي حسين; البهلول محمد (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يهدف هذا البحث إلى توصيف وتحليل أسباب تعثر السياسات الضريبية السورية وذلك في مرحلة الاصلاح الاقتصادي والضريبي. وبالاعتماد على منهج دراسة الحالة الوصفي التحليلي, يناقش البحث مراحل تطور السياسات الضريبية واستنتاج ملامحها من خلال ربطها بظروف المرحلة السياسية والاقتصادية. اعتمد تقويم السياسة الضريبية الحالية على مجموعة من المعايير الضريبية وهي: الحصيلة, العدالة, النمو الاقتصادي, الملاءمة. يستنتج الباحث ضرورة الإسراع باتخاذ إجراءات حاسمة من شأنها أن تعزز تحقيق الأهداف الاقتصادية والاجتماعية للسياسات الضريبية السورية في المرحلة القادمة ولا سيما فرض ضريبة على القيمة المضافة ثم تتبع بفرض ضريبة عامة على الدخل فضلاً عن أهمية إعادة بناء الثقة بين المكلفين والدوائر الضريبية. The study aims at describing and analyzing the reasons behind the failure of the Syrian Taxation Policies during economic and tax reformation eras. Based on a descriptive analytical case study approach, the research discusses the development phases of the tax policies to infer their crucial characteristics in relation to the political and economic context. The evaluation of the current policies has utilized a set of taxation standards such as tax yield, equality, economic growth, and relevance and simplicity. The research has concluded then that there is an urgent need to enforce vital procedures that should enhance the achievement of the forthcoming economic and social objectives of the Syrian policies. Among other, it is been suggested that value added tax and overall income tax techniques, along with restoring the mutual confidence between tax departments and taxpayers, are the most important procedures.